The Guiding Principles on Business and Human Rights: National Action Plans Toward Corporation Responsibility - Ni Ketut Supasti Dharmawan; Desak Putu Dewi Kasih; I Gede Agus Kurniawan; Putu Aras Samsithawrati (Hasanuddin Law Review, 2018)
As a global principal, corporations have the obligation to comply with national and international hard law of human rights, respect soft laws and global standards. The United Nations Guiding Principles on Business and Human Rights (GPs) of 2011 were unanimously endorsed by the Human Rights Council and are respected as a global standard that stipulates that corporations should respect human rights when conducting their business activities. The purpose of this paper is to examine the scope and focus of National Action Plans (NAPs) by comparing the Netherlands NAP on Human Rights (2013) is compared to the UK’s updated NAP of 2016 with the aim of providing ideas and good examples of a NAP for Indonesia. This study used normative legal method. It is considered to be a valuable lesson both for developed and developing countries that for practical matters it is highly important to create and implement a NAP for the implementation of the GPs. Fortunately, Indonesia in June 2017 has launched a National Action Plan on Business and Human Rights (NAP). The burden responsibility to carry out the NAP on Business and Human Rights to corporation to be implemented strongly rests on the government authorities both central government and all levels authorities, including the local level, have the duty to implement human rights obligation, including to convince corporations that upholding the GPs will ultimately be to their benefit.